More than a Gel – Hyaluronic Acid, a Central Component in the Microenvironment of Pancreatic Cancer. Issue 1 (2018) - Seufferlein, Thomas; Ducreux, Michel; Hidalgo, Manuel; Prager, Gerald; Cutsem, Eric Van
No abstract available